Kingdom come: A novel - Selim, Chandral Paulyn V. (Animo Repository, 2015)
This creative writing thesis is a novel about a group of young college boys who commit a crime that will change their lives as they know it, and will lead them to a path of destruction. This novel is an attempt to explore the hierarchies created in friendships, the fragility of identity, the complexity of attraction and morality.